An evaluation of long-term changes in alcohol use and alcohol problems among clients of the Swedish National Alcohol Helpline - Heinemans, Nelleke (BioMed Central, 2014)
BACKGROUND: The Swedish National Alcohol Helpline was developed with the intention to provide an easily available, low threshold service to hazardous and harmful alcohol users in the community. The primary aim of this study was to describe the 12-month outcome of a cohort of clients and to evaluate whether these varied as a function of the intensity of exposure to the intervention. METHODS: The alcohol use and alcohol problems of a cohort of 191 clients accessing the service between 1 April 2009 and 1 February 2011 were assessed by telephone survey at the time of the first call and after 12 months. Change in AUDIT score between baseline and follow-up was used as primary outcome. Intensity of exposure was defined by number of counselling sessions. RESULTS: At 12-month follow-up, respondents had significantly reduced their AUDIT score to half of the baseline values, and one third of the participants were abstinent or consumed alcohol at a low-risk level. Participating in more than one counselling session as compared to one session was associated with a tendency to shift to a lower AUDIT zone at follow-up among women. CONCLUSIONS: The Alcohol Helpline provides a viable community service for harmful and hazardous alcohol users. Future randomized studies including other treatment or control conditions are warranted in order to strengthen our preliminary conclusion of possible effectiveness of the counselling provided at the helpline, as well as to explore further the role of gender in moderating the treatment’s effect.